Science-technology-industry correlative indicators for policy targeting on emerging technologies: exploring the core competencies and promising industries of aspirant economies - Wong, Chan Yuan; Fung, Hon Ngen (Springer Verlag, 2017)
This paper seeks to contemplate a sequence of steps in connecting the fields of science, technology and industrial products. A method for linking different classifications (WoS–IPC–ISIC concordance) is proposed. The ensuing concordance tables inherit the roots of Grupp’s perspective on science, technology, product and market. The study contextualized the linking process as it can be instrumental for policy planning and technology targeting. The presented method allows us to postulate the potential development of technology in science and industrial products. The proposed method and organized concordance tables are intended as a guiding tool for policy makers to study the prospects of a technology or industry of interest. Two perceived high potential technologies—traditional medicine and ICT—that were sought by two aspirant economies—Hong Kong and Malaysia—are considered as case studies for the proposed method. The selected cases provide us the context of what technological research is being pursued for both fundamental knowledge and new industries. They enable us to understand the context of policy planning and targeting for sectoral and regional innovation systems. While we note the constraints of using joint-publishing and joint-patenting data to study the core competencies of developing economies and their potential for development, we realize that the proposed method enables us to highlight the gaps between science and technology and the core competencies of the selected economies, as well as their prospects in terms of technology and product development. The findings provide useful policy implications for further development of the respective cases.